An Analysis of Pronouns in Ketapang Malay Dialect: Contributions to the Development of Educational Sciences Based on Local Wisdom - M.Y., Syawaldi; Daffa Priska Febianti; Prima Duantika; Hilali Rabbani Al-Asfar (STMIK Indonesia Banda Aceh, 2025)
This study examines the types of pronouns in the Ketapang Malay dialect based on their referents. Three kinds of pronouns—personal, demonstrative, and interrogative—were used to characterise the sentences and original utterances of speakers of the Ketapang Malay dialect whose data were collected. The results demonstrate that every kind of pronoun has a unique phonological form and is employed in various social contexts, reflecting speaker intentions, geographic location, interpersonal relationships, and ownership. Interrogative pronouns display local forms of apə, siapə, manə, ŋapə, cammmanə, and bilə; demonstrative pronouns have variations like seneʔ, sənun, ɲan, bəgeneʔ, gian, and bəgian, which represent deictic distance; and personal pronouns are differentiated by number and degree of formality, such as aku, saya, kaw, sidaʔ, and diə. Possessive pronouns display a combined form with the word noʔ aku ‘mine’. Pronoun forms and functions in the Ketapang Malay dialect are abundant and reflect the social and cultural structure of the local community, according to this investigation.